Predicting voluntary contributions by “revealed-preference Nash-equilibrium” - Irenaeus Wolff (Economic Inquiry, 2025)
One-shot public-good situations are prominent in the public debate, and a prime example for behavior diverging from the standard Nash-equilibrium. Could a Nash-equilibrium predict one-shot public-good behavior in principle? A “revealed-preference Nash-equilibrium” ( rpne ) out-of-sample predicts behavior, outperforming other social-preference models. The rpne is the set of “mutual conditional contributions,” interpreting elicited conditional contributions as best-responses. Individual-level analyses confirm the results and allow for studying equilibrium selection. While the Pareto-dominant equilibrium is the modal choice, many participants use other criteria. Given the predictive positive-contributions rpne s, many real-life public-good problems may be solvable if players could coordinate on an equilibrium-selection criterion beforehand.
Keywords: 330; best-response; conditional cooperation; knowledge of preferences; Nash-equilibrium; preference stability; public good; social dilemma; social preferences